Dipeptide analogues of fluorinated aminophosphonic acid sodium salts as moderate competitive inhibitors of cathepsin C - Wątroba, Karolina; Pawełczak, Małgorzata; Kaźmierczak, Marcin (Beilstein Journal of Organic Chemistry, 2023)
In this paper, we present the solvolysis reaction of dipeptide analogues of fluorinated aminophosphonates with simultaneous quantitative deprotection of the amino group. To the best of our knowledge, this work is the first reported example of the application of fluorinated aminophosphonates in cathepsin C inhibition studies. The new molecules show moderate inhibition of the cathepsin C enzyme, which opens the door to consider them as potential therapeutic agents. Overall, our findings provide a new avenue for the development of fluorinated aminophosphonate-based inhibitors.
Keywords: aminophosphonates; cathepsin C; dipeptide; fluorine; solvolysis